Kesenjangan Representasi Politik Perempuan: Analisis Gender di Tingkat Desa dan Kota - Batubara, Annisa Ismaida (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
The gap in women’s political representation at the village and city levels remains a crucial issue in Indonesian democratic discourse, as women’s representation does not fully reflect the principle of gender equality. Although regulations such as a 30 percent quota for women’s representation have been established, their implementation is often merely formal. It does not translate into increased participation by women in decision-making structures. This study aims to analyze the factors influencing the gap in women’s political representation by comparing conditions at the village and city levels through a gender analysis perspective. The research method employed is a qualitative descriptive approach, utilizing a library-based approach that incorporates secondary data from academic literature, research reports, government regulations, and statistical data related to women’s political involvement. The results indicate that the gap in women’s representation at the village level is more influenced by a strong patriarchal culture, low access to political education, and the dominance of local elites that limit women’s freedom of movement. Meanwhile, at the city level, obstacles are more caused by transactional political practices, the dominance of economic capital, and institutional biases within the still masculine structure of political parties. However, there are also opportunities at both levels, such as increased public awareness of the importance of women’s political participation, the presence of women’s organizational networks, and regulatory support that encourages more equitable representation. The research conclusion confirms that the gap in women’s political representation is a multidimensional problem that requires intervention through political education, party reform, and strengthening of affirmative regulations so that gender equality in politics can be realized substantively.